HSP90 affects root growth in Arabidopsis by regulating the polar distribution of PIN1 - Samakovli, Despina; Roka, Loukia; Dimopoulou, Anastasia; Plitsi, Panagiota Konstantinia; Žukauskait, Asta; Georgopoulou, Paraskevi; Novák, Ondřej; Milioni, Dimitra; Hatzopoulos, Polydefkis (The New phytologist, 2021)
Auxin homeostasis and signaling affect a broad range of developmental processes in plants. The interplay between HSP90 and auxin signaling is channeled through the chaperoning capacity of the HSP90 on the TIR1 auxin receptor. The sophisticated buffering capacity of the HSP90 system through the interaction with diverse signaling protein components drastically shapes genetic circuitries regulating various developmental aspects. However, the elegant networking capacity of HSP90 in the global regulation of auxin response and homeostasis has not been appreciated. Arabidopsis hsp90 mutants were screened for gravity response. Phenotypic analysis of root meristems and cotyledon veins was performed. PIN1 localization in hsp90 mutants was determined. Our results showed that HSP90 affected the asymmetrical distribution of PIN1 in plasma membranes and influenced its expression in prompt cell niches. Depletion of HSP90 distorted polar distribution of auxin, as the acropetal auxin transport was highly affected, leading to impaired root gravitropism and lateral root formation. The essential role of the HSP90 in auxin homeostasis was profoundly evident from early development, as HSP90 depletion affected embryo development and the pattern formation of veins in cotyledons. Our data suggest that the HSP90-mediated distribution of PIN1 modulates auxin distribution and thereby auxin signaling to properly promote plant development.
Keywords: Arabidopsis Proteins; gravitropism; Membrane Transport Proteins; cotyledon veins; root meristem; HSP90 Heat-Shock Proteins; membránové transportní proteiny; Indoleacetic Acids; proteiny huseníčku; cell size; proteiny tepelného šoku HSP90; Plant Roots; kyseliny indoloctové; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; lateral roots; PIN1; auxin transport; Arabidopsis; kořeny rostlin; embryo development